Scrap Car Tires Gasification at High Pressure in Atmosphere of Steam and Carbon Dioxide; AIP Conference Proceedings; Vol. 2422 : Heat and mass transfer in the thermal control system of technical and technological energy equipment (HMTTSC 2021) - Slusarskiy (Slyusarsky) K. V. Konstantin Vitalievich (Heat and mass transfer in combustion technology, 2021)
Title screen